Efisiensi ISO 27001, ISO 9001, dan Standar LPSE pada Data Center dan e-Procurement Pemerintahan - Faradina Harumi; Lukito Edi Nugroho; Sri Suning Kusumawardani (UIN Sunan Kalijaga Yogyakarta, 2021)
National government and regional government are developing public service by communication and information network. Provided public service must be reliable, trusted, and reachable. To fulfil that, there are standards that need to be implemented for example ISO 27001, ISO 9001, and LPSE Standard. The purpose of this paper is to create efficiency in implementing ISO 27001, ISO 9001, and LPSE Standard with the scope of data center infrastructure and e-procurement service (LPSE). This paper uses qualitative method. The data obtained from primary and secondary data through a case study from government that has successfully implemented those standards. The result of this paper is mapping that shows intersection of similarity and difference between ISO 27001:2013, ISO 9001:2015, dan LPSE Standard and efficiency of document requirement which previously 50 to 24 documents only.